FRACTURE BEHAVIOUR OF THE BASALT FIBRE REINFORCED COMPOSITES WITH POLYSILOXANE-DERIVED MATRIX - Glogar P.; Černý M.; Tolde Z. (My University, 2007)
Selected mechanical properties of unidirectional composites with polysiloxane-derived matrix and continuous basalt fibres reinforcement are presented. A special attention is devoted to the impact of long term exposition in hot air (aimed as a simulation of the anticipated operating conditions) to the composite failure under flexural load. The investigated composites worsened their properties after treatment in air at elevated temperature (650 – 750 °C). The originally non-catastrophic flexural failure changed to a brittle fracture, which was accompanied with a flexural strength decrease. The coalescence of fibres and their strong interaction with the matrix are probably the main reasons for the onset of brittleness. Unless these drawbacks are resolved the service temperature of the composites in air will probably not exceed approximately 500 °C.
Keywords: BASALT FIBRE; COMPOSITE; FRACTURE BEHAVIOUR; POLYSILOXANE; PRECURSOR